2004
DOI: 10.1002/ar.b.20019
|View full text |Cite
|
Sign up to set email alerts
|

Traditional teaching supported by computer‐assisted learning for macroscopic anatomy

Abstract: Over the years we have observed that there is a very low passing rate for the Anatomy and Neuroanatomy courses in our department, and for that reason we decided to implement the use of student-learning resources. The objective of this study was to compare the results of traditional methodology with those obtained with the support of computer-assisted learning (CAL). We performed a retrospective and joint study for Anatomy and Neuroanatomy groups during the period of September 2001 to February 2003, to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 14 publications
4
51
1
6
Order By: Relevance
“…The conventional teaching and learning of mathematics over-emphasizes algebraic methods, and the students had been trained to use such methods to solve most mathematics problems. However, the use of a graphing calculator can change the teaching and learning of calculus concepts from relying solely on algebraic method to encompassing numeric, algebraic and graphical methods, as indicated by Elizondo [11]. Several studies have shown that the connection of International Journal of Mathematical Education in Science and Technology different representations leads to the development of conceptual understanding and the improvement of students' problem-solving skills [12].…”
Section: Discussion:-mentioning
confidence: 99%
“…The conventional teaching and learning of mathematics over-emphasizes algebraic methods, and the students had been trained to use such methods to solve most mathematics problems. However, the use of a graphing calculator can change the teaching and learning of calculus concepts from relying solely on algebraic method to encompassing numeric, algebraic and graphical methods, as indicated by Elizondo [11]. Several studies have shown that the connection of International Journal of Mathematical Education in Science and Technology different representations leads to the development of conceptual understanding and the improvement of students' problem-solving skills [12].…”
Section: Discussion:-mentioning
confidence: 99%
“…Looking at the effects of traditional anatomy teaching to computer assisted learning (CAL), there was a significant difference in final exam results with those students who had been taught traditionally with CAL than those with traditional teaching alone (Elizondo-Oma~na et al, 2004). However, medical students in Mexico who used online resources spent an extra 20 hours learning anatomy and Neuroanatomy (Elizondo-Oma~na et al, 2004); the difference in exam results and student performance improvement may be due to the fact that these students were exposed to learning material for longer period of time, rather than the mode of learning or the difference in teaching methods.…”
Section: New Methods Of Teaching In Medical Schoolsmentioning
confidence: 99%
“…However, medical students in Mexico who used online resources spent an extra 20 hours learning anatomy and Neuroanatomy (Elizondo-Oma~na et al, 2004); the difference in exam results and student performance improvement may be due to the fact that these students were exposed to learning material for longer period of time, rather than the mode of learning or the difference in teaching methods.…”
Section: New Methods Of Teaching In Medical Schoolsmentioning
confidence: 99%
“…Through interactive material in digital repository, immediate feedback and problem solving activities it can catalyse active participation [4,5]. Through computer enabled three-dimensional visualization, it can offset the limitations of verbal descriptions in teaching anatomy [6][7][8][9][10]. For the current tech-savvy generation, it can offer a platform to study through a media they enjoy.…”
Section: The Effectiveness Of Early Clinical Exposure and E-learning mentioning
confidence: 99%
“…In a large retrospective study done by Elizondo-Omana et al, students taught using traditional method had lower averages and lower percentage of passing than those taught using additional CAL (Computer Assisted Learning) [6]. They attribute it to students spending an additional 20 hours on the multimedia resources in the semester.…”
Section: Total Scoresmentioning
confidence: 99%